Second language acquisition and the younger learner child's play? - Philp, Jenefer ca. 20./21. Jh; Oliver, Rhonda; Mackey, Alison 1966- (Language learning & language teaching, 2008)
This new volume of work highlights the distinctiveness of child SLA through a collection of different types of empirical research specific to younger learners. Characteristics of children's cognitive, emotional, and social development distinguish their experiences from those of adult L2 learners, creating intriguing issues for SLA research, and also raising important practical questions regarding effective pedagogical techniques for learners of different ages. While child SLA is often typically thought of as simple (and often enjoyable and universally effortless), in other words, as "child's p